2007
DOI: 10.1080/00036840600592908
|View full text |Cite
|
Sign up to set email alerts
|

Risk coping and starvation in rural China

Abstract: We use a 3-year panel from two poor provinces in Southern China to examine the nature of risks to which rural households are exposed and their ability to insure calorie consumption and spending of total consumption against idiosyncratic shocks to their income. We find that idiosyncratic risks are indeed the main source of income variation in the sample, consumption is better insured than total spending. Unlike total spending where full insurance is rejected in most cases, calorie intake is completely insured f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
(65 reference statements)
1
8
0
Order By: Relevance
“…A bold conjecture is that China's potential to improve agricultural productivity may be realized if the fragmented land parcels can be consolidated into larger farms, where modern technologies can be easily applied. Deininger, Jin, and Yu (2007) found that access to land offers rural Chinese households protection against idiosyncratic risks. Deininger and Jin (2005) show that decentralized land rent markets might contribute to both equity and efficiency and have advantages over administrative reallocation.…”
Section: Discussionmentioning
confidence: 99%
“…A bold conjecture is that China's potential to improve agricultural productivity may be realized if the fragmented land parcels can be consolidated into larger farms, where modern technologies can be easily applied. Deininger, Jin, and Yu (2007) found that access to land offers rural Chinese households protection against idiosyncratic risks. Deininger and Jin (2005) show that decentralized land rent markets might contribute to both equity and efficiency and have advantages over administrative reallocation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, precautionary food storage has been found to vary with income level of households (Jalan and Ravallion, 2001;Deininger et al, 2007;Carter and Lybbert, 2012; Michler and Balagtas, Ho: 2 = 3 = 4 = 0; ***and ** = significant at 1 and 5%, respectively. 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Even when prices are anticipated to rise with a high level of certainty, such households still fail to store food to get arbitrage profits. Deininger et al (2007) argued that the concern for food security motivates household storage even when arbitrage is unlikely to insure food *Corresponding author. Email: Charles.Owach@fao.org.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive literature exists regarding the value of precautionary storage of staple grains. In addition to its value as self‐insurance, staple grain storage provides households with a price hedge (Park, ) and helps ensure food security (Deininger et al., ; Renkow, ; Saha and Stroud, ). These examples of what Working () referred to as the convenience yield of grain storage suggest that the motivation for precautionary storage, and by extension the market failures that storage addresses, may be different from the motivation for other forms of precautionary savings.…”
Section: Introductionmentioning
confidence: 99%